When Poor Light‐Emitting Spiro Compounds in Solution Turn into Emissive Pure Layers in Organic Light‐Emitting Diodes: The Key Role of Phosphine Substituents - Pauline Tourneur; Fabien Lucas; Clément Brouillac; Cassandre Quinton; Roberto Lazzaroni; Yoann Olivier; Pascal Viville; Cyril Poriel; Jérôme Cornil (Advanced Photonics Research, 2022)
Spiro compounds are widely used as host matrices in organic light‐emitting diodes (OLEDs). Here, inspired by the recent developments in thermally activated delayed fluorescence (TADF) materials, the potential as a light emitter of two spiro‐configured organic semi‐conductors is investigated, constructed by the association of quinolinophenothiazine (QPTZ) or indoloacridine (IA) as the electron‐rich fragment and diphenylphosphine oxide fluorene as the electron‐poor fragment. By comparison with structural analogues lacking phosphine oxides, the crucial role played by these electron‐accepting substituents not only on the photo‐physical properties but also on the device performances is evidenced. Despite a very low quantum yield in solution, these two compounds unexpectedly display good emission properties when incorporated as a pure layer in OLEDs, thus highlighting the role of intermolecular effects.